MEDIA KOTAK CAHAYA UNTUK MENINGKATKAN PEMAHAMAN DAN HASIL BELAJAR IPA PADA PEMBELAJARAN TATAP MUKA TERBATAS - Meirza Nanda Faradita; Anita Rachman Ainur Rofiqoh (PROCEEDING UMSURABAYA, 2022)
Science is a very important subject to be studied at the elementary level because it discusses events related to nature and the lives of students. The problem that often occurs is the low learning outcomes of students, especially in science subjects on the properties of light. When the teacher explains the material properties of light in class, many students do not understand, because students do not focus and feel bored with the lecture method. This study aims to determine the process of understanding and improving learning outcomes by using light box teaching aids for fourth grade elementary school students. This research was conducted in the fourth grade of SD at MI Al-Hidayah Surabaya with a total of 30 students. This research is a classroom action research. This research was conducted in two cycles. Many students do not understand the material and cannot explain in their own language so that the average score obtained by students at the pre-cycle stage is 53.1. After the action was carried out using light box props in the first cycle, the student's score increased to 73.5. Because it has not reached the KKM score of 75, cycle II is carried out. At the stage of the second cycle, students experienced an increase above the KKM, namely 86.7. The improvement in the second cycle has reached the target. This is proven by student achievement, so it can be concluded that the use of light box teaching aids can improve students' understanding and learning outcomes.Â Keywoards: understanding, learning outcomes, media